Travels in the Tian'-Shan' : 1856-1857 - Semenov-Ti͡anʹ-Shanskiĭ, Petr, 1827-1914 (Works issued by the Hakluyt Society, 1998)
Accompanied by only a serf servant, in May 1856, Semenov embarked on an 18-month journey from St Petersburg through Kazan' to Semipalatinsk, and thence via the Altai to the newly established Russian settlement of Vernoe (later Alma-Ata, now Almaty). (Dust jacket).